1993
DOI: 10.1002/macp.1993.021940310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and non‐linear optical characteristics of crosslinked and linear epoxy polymers with pendant tolane chromophores

Abstract: Linear and crosslinked epoxy polymers containing high concentrations (ca. 86 wt.-Yo) of pendant 4-(4-nitrophenylethynyl)aniline [4-amino-4'-nitrotolane] chromophores were synthesized. They exhibit a smectic phase in the bulk once heated above the glass transition temperature (ca. 70°C). The appearance of the highly scattering smectic phase could be avoided by starting the crosslinking process of thin polymer films in the presence of solvent. Application of corona poling during crosslinking resulted in a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…26 This nitration yielded 1-iodo-3,4-dinitrobenzene ( 1 ), which was then reduced using Sn over HCl to yield 1-iodobenzene-3,4-diamine ( 2 ). 27 Then, the diamine was reacted with 2,5-dihydroxy-1,4-benzoquinone in ethanol to produce 7-iodo-2,3-bis(hydroxyl)phenazine ( 3 ), which was further alkylated without purification. 7-Iodo-2,3-bis(octyloxy)phenazine ( 4 ) was then used in a Sonogashira coupling reaction with triisopropylsilyl (TIPS) acetylene to yield 7-triisopropylsilylethynyl-2,3-bis(octyloxy)phenazine ( 5 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…26 This nitration yielded 1-iodo-3,4-dinitrobenzene ( 1 ), which was then reduced using Sn over HCl to yield 1-iodobenzene-3,4-diamine ( 2 ). 27 Then, the diamine was reacted with 2,5-dihydroxy-1,4-benzoquinone in ethanol to produce 7-iodo-2,3-bis(hydroxyl)phenazine ( 3 ), which was further alkylated without purification. 7-Iodo-2,3-bis(octyloxy)phenazine ( 4 ) was then used in a Sonogashira coupling reaction with triisopropylsilyl (TIPS) acetylene to yield 7-triisopropylsilylethynyl-2,3-bis(octyloxy)phenazine ( 5 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…To suppress this reorientation, rigid polymer backbones exhibiting high T g 's were synthesized. This can be achieved either in cross‐linked systems2–11 or with thermoplastics like polyimides12–17 or maleimide‐based polymers 18–28…”
Section: Introductionmentioning
confidence: 99%
“…It has often been observed that poled NLO polymer materials undergo temporal relaxation of the dipolar orientation, which so far has prevented their use in practical EO devices. During the past decade, research has focused on improving the temporal stability of the polar order via the synthesis of high‐glass‐transition‐temperature ( T g ) polymers or the creation of thermocrosslinked or photocrosslinked polymer networks after poling,3–13 both exhibiting high thermal stability for the EO coefficients. However, their processing is usually rather difficult.…”
Section: Introductionmentioning
confidence: 99%